Collaboration in winter vehicle testing - real-time simulations boosting innovation opportunities - Nybacka, Mikael; Larsson, Tobias; Ericson, Åsa (Luleå University of Technology, 2007)
The performance of cars has during recent years become increasingly dependent on complex electronic systems used especially for safety but also comfort, performance and informatics. Automotive winter testing activities in northern Sweden is vital to test and try out those systems. A contradiction to increased performance is that faulty software also causes 30 % of severe malfunctions in the functionality of the car. To deal with these problems, as early in the design process as possible, innovative methods to cope with digital abstraction and the physical world in a unified way seems promising. One useful approach, in automotive winter testing, might be to support the possibilities for real-time vehicle simulations of the car in motion. The closer collaboration in the automotive industry might be an incitement for investing in technologies for knowledge sharing. Besides enhancing the product development process, additional knowledge might support innovations. Today, instead of providing parts similar to their competitors and relying on one or two automakers, successful suppliers focus heavily on innovation and on collaboration with a number of manufacturers on a global market. Due to the possibilities to visualize whole processes, the use of simulations seems to support a' seeing first' approach to innovations. Thus, the purpose of this paper is to describe an as-is scenario and a to-be scenario for automotive winter testing to highlight how the use of real-time simulations facilitates innovative methods 10.1007/978-0-387-75456-7_21 CASTT - Center for Automotive Winter Testing